Vaginal Lactobacillus iners abundance is associated with outcome in antibiotic treatment of bacterial vaginosis and capable of inhibiting Gardnerella - Zhou, Rui; Lu, Jingjing; Wang, Jun; Xiao, Bingbing (Frontiers in Cellular and Infection Microbiology, 2022)
Bacterial vaginosis is characterized as a polymicrobial dysbiosis with the loss of Lactobacillus spp. and growth of multiple anerobic bacteria, including Gardnerella, Prevotella and Atopobium ranked as the top three most abundant. A total of nine Gardnerella genomospecies have been identified, yet the association between their distribution or any exact Lactobacillus species with BV occurrence or prognosis remains controversial. A total of 308 patients and 62 healthy women who sought annual examinations were recruited, with 130 BV patients and 41 healthy women who met our inclusion criteria finally included. Vaginal samples were used for microscopic examination, 16S rRNA sequencing, bacterial culture and isolation. Isolates of Gardnerella vaginalis, Fannyhessae vaginae (used to be called Atopobium vaginae) and Lactobacillus iners were used for competition tests. We found that the relative abundances of Gardnerella, Prevotella and Atopobium were elevated in BV patients compared to healthy people (p<0.0001), yet no significant differences were found among patients with different clinical outcomes (p>0.05). Seven out of nine Gardnerella genomospecies were present in both BV patients and healthy women, and the relative abundances of all detected genomospecies were higher in BV patients (p<0.05). Cured patients possessed higher GS03 than intermediate and failed patients (p=0.005, 0.0337). L. iners was significantly higher in cured patients than in the other two groups (p=0.0021, p<0.0001), and its ability to inhibit the growth of G. vaginalis and F. vaginae was validated. In summary, seven Gardnerella genomospecies were detected in Chinese BV patients, but no association of its distribution and BV occurrence or prognosis was found. The relative abundance of L. iners was higher in cured patients, and its antimicrobial activity against G. vaginalis and F. vaginae was validated through in vitro inhibition experiment. L. iners could become a predictive indicator of clinical outcomes of BV patients, and its antimicrobial function might be beneficial to BV patients.